2004
DOI: 10.1021/jp0471960
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Chemistry of CH3 on Si/Cu(100); the Role of Sn as a Promoter

Abstract: The effect of tin on the thermal chemistry of CH 3 on Si/Cu(100) was investigated using temperature programmed desorption (TPD), X-ray photoelectron spectroscopy (XPS), ion scattering spectroscopy (ISS), low energy electron diffraction (LEED), Auger electron spectroscopy (AES), and high-resolution helium atom scattering (HAS). The Si/Cu(100) substrate was prepared by exposure to silane at 420 K. The TPD results showed that (CH 3 ) 3 SiH was the dominant product desorbing from Si/Cu(100) after exposure to CH 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It would seem that the addition of Sn helps to stabilize CH 3 in this reaction. Zhang et al 15 studied the influence of Sn on the thermal chemistry of CH 3 on the Si/ Cu(100) surface and showed that the presence of Sn inhibited the decomposition of CH 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would seem that the addition of Sn helps to stabilize CH 3 in this reaction. Zhang et al 15 studied the influence of Sn on the thermal chemistry of CH 3 on the Si/ Cu(100) surface and showed that the presence of Sn inhibited the decomposition of CH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the complexity of this reaction, the actions of promoters are still not clearly understood. Some studies focused on the surface species and have utilized many experimental techniques to characterize the effects of promoters. Yet, we think that more attention should be paid to the key intermediate in this reaction, the Cu 3 Si alloy phase. Many researchers, e.g., Klebanski and Voorhoeve, have suggested that the Cu 3 Si alloy phase (η phase in the Cu–Si phase diagram) is the active site in which DMDC is selectively produced.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has also used a variety of surface analytical techniques to investigate the DS catalyst after reaction [11][12][13][14][15][16][17]. Missing from prior research, however, has been in situ studies that investigate the working surface of the DS contact mass under reaction conditions.…”
Section: Introductionmentioning
confidence: 99%